Hepatoid adenocarcinoma of the lung with PD-L1 expression and the response to anti-PD-1 therapy: a case report - Li, Yan; Liu, Lili; Wang, Dongfeng; Tan, Xiaojing; Sui, Yanmin; Yang, Honglan (Frontiers in Oncology, 2023)
Hepatoid adenocarcinoma of the lung (HAL) is extremely rare; a standardized treatment strategy for HAL has not been established. The prognosis of patients with unresectable HAL is extremely poor. Here, we reported a 64-year-old male patient with unresectable alpha-fetoprotein-producing HAL who showed moderate harboring programmed death ligand 1 (PD-L1) expression and no targetable driver mutations. The patient was treated with brain radiotherapy, multiple lines of chemotherapies, and PD-1 inhibitor and achieved a survival rate of 9 months. The patient finally died because of the progression of brain metastasis. The case report provides valuable information for the treatment strategy development of advanced HAL patients and reminds us of the therapeutic particularity of brain metastasis.